A Hierarchical Integration of Normal and Abnormal Personality Dimensions: Structure and Predictive Validity in a Heterogeneous Sample of Psychiatric Outpatients. (June 2020) - Allen, Timothy A.; DeYoung, Colin G.; Bagby, R. Michael; Pollock, Bruce G.; Quilty, Lena C.
Hierarchical, quantitative models of psychopathology focus primarily on higher-order constructs, whereas less is known about the structure and content comprising lower-order dimensions of psychopathology. Here, we address this gap in the literature by using targeted factor analysis to integrate the 25 maladaptive facet-level traits of the Personality Inventory for Diagnostic and Statistical Manual of Mental Disorder–Fifth edition and the 10 aspect-level traits of the normal personality hierarchy within a sample of 198 psychiatric outpatients. A 10-factor solution replicated previous work, with each of the 10 aspects primarily characterizing only one factor. In addition, the 10 factors differentially predicted a range of diagnoses, including alcohol use disorder, major depression, panic disorder, social anxiety, and borderline and avoidant personality disorders. Our results suggest that research on the development, causes, and structure of lower-order traits within the normal personality hierarchy may serve as an important guide to research on the causes and structure of maladaptive personality.